THE PROBLEMS OF WASTE MANAGEMENT IN PEMALANG REGENCY - moh sidik (Journal Philosophy of Law, 2021)
This study aims to determine the implications of Pemalang Regency Regulation Number 13 of 2012 on implementing waste management. Garbage is an environmental problem that until now has received serious attention in Indonesia. In implementing waste management, local governments have the authority to formulate regional regulations and provide waste management facilities how the success of waste management in Pemalang Regency can be known through the implementation of waste management based on Pemalang Regency Regulation Number 13 of 2012. The research method used in this study is an empirical juridical method by examining the applicable legal provisions and what happens in reality on the ground. The sources used to consist of primary and secondary sources. The results of this study indicate that Pemalang Regency Regulation Number 13 of 2012 substantially regulates the technical and responsibilities of each individual or institution in waste management, as well as sanctions for waste management violators. Implementing waste management based on Pemalang Regency Regulation No. 13 of 2012 still found many obstacles in the form of a limited budget, human resources, and low public awareness. The authority for waste management given to the village government is also still limited. In general, the background of the emergence of these obstacles is caused by the limitations of the government in providing facilities and local regulations that do not give authority to the village government ideally.